Myoepithelial Carcinoma: The Role of Radiation Therapy. A Case Report and Analysis of Data From the Surveillance, Epidemiology, and End Results (SEER) Registry. Issue 4 (May 2016) - Miccio, Joseph A.; Oladeru, Oluwadamilola T.; Yang, Jie; Xue, Yaqi; Hoda, Syed T.; Ryu, Samuel; Stessin, Alexander M.; Parker, Robert I.
Abstract : Purpose/Objective: The role of radiation therapy in the treatment of myoepithelial carcinoma (MC) is unknown. We present a case of a high-grade soft-tissue MC in a pediatric patient and retrospectively examine the effect of postoperative radiation on survival in patients with MC. Materials and Methods: Our patient was treated with 4 cycles of ifosfamide, cisplatin, and etoposide followed by 3 cycles of ifosfamide vincristine and etoposide. Radiation was delivered to a total dose of 5580 cGy in 180 cGy/fraction to the surgical bed with a 2 cm margin starting after the third cycle of chemotherapy. The Surveillance, Epidemiology, and End Results (SEER) registry database was queried for cases of surgically resected MC. Retrospective analysis was performed with the endpoint of overall survival (OS). Results: Two hundred thirty-four cases of MC were identified; for 62 of these cases, the grade of the tumor wasidentified. Of these 62 patients, 27 received postoperative radiation. OS was improved with adjuvant radiation therapy in patients with grade III or IV MC ( P <0.01) as determined by the log-rank test. Conclusions: This analysis of SEER data showed an OS benefit with adjuvant radiation therapy in the treatment of high-grade MC. Physicians should report all cases of MC to improve clinical decision making in the treatment of this rare disease.